Alcohol Use and Drinking Motives Among Sanctioned and Nonsanctioned Students. Issue 2 (July 2017) - Doumas, Diana M.
Abstract : This study examined differences in the relationship of drinking motives to drinking behavior among sanctioned and nonsanctioned 1st‐year students ( N = 298). Results of hierarchical regression analyses indicated that for both sanctioned and nonsanctioned students, alcohol use was predicted by social and enhancement motives, and alcohol‐related consequences were predicted by social, enhancement, and coping motives. High levels of conformity motives predicted alcohol use and alcohol‐related consequences for sanctioned students only. Counseling implications are discussed.